TEAM BASED LEARNING: EXPERIENCE REPORT IN THE SUBJECT OF INTEGRATED CLINIC IN DENTISTRY GRADUATION - Costa, Sarah Teixeira (2022)
The present work aims, through an experience report, to describe the planning, execution and development of concepts related to subjects already taught in the Dentistry course, using TBL as a teaching methodology. At first, in a classroom setting, students individually answered questions selected by the professors of previous ENADE tests. All questions chosen had a clinical and interdisciplinary nature. After preliminary correction by teachers, without disclosing the results, students were divided into small groups to debate each of the questions and answers they chose, reaching consensus for the presentation of a single answer by the group. The interpretation of the results, as well as the comparison of group and individual scores, allowed us to infer that the TBL was very useful in the learning process and in the assessment of academic training. Students exercised their communication, argumentation and persuasion skills, improving their interaction with peers, with teachers and personal performance. Teachers and students were able to interact in a playful way, in addition to understanding the level of assimilation of previous content and its possible application in the subject to be studied. The teachers' understanding of the students' level of knowledge facilitated patients selection to be treated, ensuring technical excellence and satisfaction of the entire service delivery chain.